Role of Auxin and Nitrate Signaling in the Development of Root System Architecture - Hu, Qi-Qi; Shu, Jian-Qin; Li, Wen-Min; Wang, Guang-Zhi (Frontiers in Plant Science, 2021)
Plant root is an important storage organ that accumulates indole-3-acetic acid (IAA), an auxin transported from the apical meristem, and nitrogen obtained from the outside environment, thus serving as a strategic reserve. IAA and nitrogen also act as signaling molecules to stimulate downstream factors that promote root growth for obtaining more resources. Given the fluctuations in the soil environment, the uneven distribution of nitrogen induces plants to develop a set of strategies that effectively improve nitrogen use efficiency. Auxin integrates the information regarding the nitrate status inside and outside the plant body to reasonably distribute resources and sustainably construct the plant root system. In this review, we focus on the main factors involved in the process of nitrate- and auxin-mediated regulation of root structure, to better understand how the root system integrates the internal and external information and how this information is utilized to modify the root system architecture.